Eigenvalue analyses for non-transposed three-phase transmission line considering non-implicit ground wires - Monzani, R. C. [UNESP]; Prado, A. J. [UNESP]; Kurokawa, S. [UNESP]; Bovolato, L. F. [UNESP]; Pissolato Filho, J. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
This paper presents a method for analyzing electromagnetic transients using real transformation matrices in three-phase systems considering the presence of ground wires. So, for the Z and Y matrices that represent the transmission line, the characteristics of ground wires are not implied in the values related to the phases. A first approach uses a real transformation matrix for the entire frequency range considered in this case. This transformation matrix is an approximation to the exact transformation matrix. For those elements related to the phases of the considered system, the transformation matrix is composed of the elements of Clarke's matrix. In part related to the ground wires, the elements of the transformation matrix must establish a relationship with the elements of the phases considering the establishment of a single homopolar reference in the mode domain. In the case of three-phase lines with the presence of two ground wires, it is unable to get the full diagonalization of the matrices Z and Y in the mode domain. This leads to the second proposal for the composition of real transformation matrix: obtain such transformation matrix from the multiplication of two real and constant matrices. In this case, the inclusion of a second matrix had the objective to minimize errors from the first proposal for the composition of the transformation matrix mentioned. © 2012 IEEE.
Keywords: eigenvalue; eigenvector; electromagnetic transients; ground wires; homopolar mode; line transmission; Clarke's matrix; Constant matrix; Diagonalizations; Eigen-value; Eigenvalue analysis; Electro-magnetic transient; Frequency ranges; Ground wire; Mode domain; Real transformation; Three phase system; Three-phase lines; Transformation matrices; Eigenvalues and eigenfunctions; Electric lines; Transients; Transmission line theory; Wire; Linear transformations